A Comparison of Financial Liquidity Ratios in the Polish and Czech Industrial Processing Sector for Micro, Small, Medium and Large Business Entities - Maślanka, Tomasz; Mazur-Maślanka, Iwona (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
The publication presents the development of financial liquidity ratios (current and increased) in the Polish and Czech industrial processing sectors for micro, small, medium and large business entities. The analyses are based on the financial data of companies taken from the Amadeus database for the years 2006–2014.In all of the groups of enterprises analysed in both countries, an increase in the liquidity ratios occurred. The mean values of the indicators were significantly more volatile than the median among all groups of companies. Large entities reported the lowest values of both indicators, both in Poland and in the Czech Republic.